HRM and TQM: association with job involvement - Boon, Ooi Keng; Arumugam, Veeri; Safa, Mohammad Samaun; Bakar, Nooh Abu (EMERALD GROUP PUBLISHING LIMITED, 2007)
Purpose - The purpose of this paper is to examine the perceptions of individual employees on the influence of eight elements of HRM/TQM (i.e. leadership, training and development, employee participation, reward and recognition, customer focus, empowerment, teamwork, and communication) on employees' job involvement in six major Malaysian semiconductor contract manufacturing organizations. Despite extensive research and voluminous literature on HRM/TQM, very little empirical research has examined this scope of investigative study. Therefore, the hypotheses are developed with the intention of examining this relationship.